A gestão escolar e o processo de inclusão de crianças com deficiência na educação infantil: um estudo no município de Feira de Santana – BA - Santos, Cristiane Sousa (2021)
The inclusion of children with disabilities in Early Childhood Education has gained prominence in discussions in the educational field at national and/or international levels. Faced with this movement, Early Childhood Education, the first stage of Brazilian Basic Education, in recent years, has shown a considerable growth in enrollment of children aged 0-5 years, the target audience of Special Education, in regular schools. In view of this, the management team has an important role in the inclusion process, both in administrative and pedagogical aspects. Thinking about the role of the management team in Early Childhood Education schools, this research sought to understand the role of the management team in the process of inclusion of children with disabilities, in the context of a Municipal Early Childhood Education Center located in the city of Feira de Santana/BA. Therefore, it is proposed to adopt the principles of qualitative research methodology, approaching the case study, using a questionnaire and semi-structured interview for the collection of data with the management team (director and pedagogical coordinator), as well as teachers, about the highlighted object of study. The specific objectives raised for this research were: a) to describe the understanding of the management and teaching team about the process of school inclusion of children with disabilities in early childhood education; b) identify the elements of school management necessary to carry out processes of school inclusion of children in early childhood education; c) identify the actions developed by the School Management to promote the inclusion of children with disabilities in a Municipal Child Education Center in Feira de Santana; d) characterize the continuing education process of the management team that integrates the Child Education Center, with regard to the process of school inclusion of children with disabilities. From the data collected, categories were established to be analyzed: Category 1: Understanding the process of inclusion of children with disabilities in early childhood education; Category 2: Elements of School Management necessary to carry out processes of school inclusion of children in early childhood education; Category 3: Actions developed by School Management to promote the inclusion of children with disabilities in a Municipal Child Education Center in Feira de Santana; Category 4: Continuing Education. The research findings reveal that, despite the initiatives in favor of inclusion carried out by the management team in partnership with teachers and families, according to the subjects, there is a need to advance in the provision of on-the-job training, expansion of accessibility, guarantee of adapted materials, which has made it impossible for inclusion to actually happen. It is concluded that the inclusion of children with disabilities in Early Childhood Education is still a challenge, especially for the management team, which ranges from the understanding of inclusive school by education professionals and the family, to government investment through public policies for teacher training, investment in careers and guarantee of resources, actions which, when carried out, can contribute to the development of autonomy and learning of children at an early age within the inclusion process.